Literasi Hukum Digital: Studi Deskriptif Pengetahuan UU ITE 2024 pada Generasi Z di Kota Semarang - Priyo Wibowo; Yohanes Yupilustanaji (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The rapid growth of Generation Z's digital activities on social media has increased exposure to various risks, including oversharing, cyberbullying, the spread of misinformation, and privacy violations. Consequently, digital literacy should emphasize not only technical competencies but also a comprehensive understanding of cyber law. This study aims to explore digital legal literacy by mapping Generation Z's level of knowledge regarding Indonesia's Electronic Information and Transactions Law (ITE Law No. 1 of 2024, Second Amendment) in Semarang City. A quantitative descriptive approach was employed. Primary data were collected through an online questionnaire administered to 510 valid respondents aged 16–24 years, predominantly those aged 18–20 years (66.5%), using a convenience sampling technique with a margin of error of 4.42%. The data were analyzed using descriptive statistics with IBM SPSS software. The findings reveal that 57.3% of respondents reported daily screen time exceeding six hours. Most respondents demonstrated moderate to high levels of knowledge in the digital citizenship dimension, particularly regarding the boundaries of doxing behavior (Mean = 2.91). In contrast, the level of cyber law awareness remained relatively low, especially concerning legal sanctions for spreading hoaxes (Mean = 1.85) and knowledge of the revised ITE Law (Mean = 2.12). These findings highlight the importance of integrating cyber law education into a competency-based digital citizenship curriculum to equip Generation Z with the knowledge and skills needed to engage in responsible, safe, and legally compliant behavior in the digital environment.